(untitled) (Zien Journal of Social Sciences and Humanities, 2023)
In this article, the unique features of Abdulla Qadiri’s views on Jadidism were written, and the poems of Abdulla Qadiri such as "Tuy", "Ahvolimiz" are artistically analyzed. Also, the article clearly reflects Abdulla Qadiri’s ability to use words in poetic verses.